PENERAPAN PEMBELAJARAN TEKS PERSUASIF MENGGUNAKAN MODEL KOOPERATIF STUDENT TEAM ACHIEVMENT DIVISION - Farhah Salsabil Yumna; Latifah; R. Ika Mustika (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
The learning outcomes of SMPN 3 Ngamprah students in learning Indonesian, especially persuasive text material, received unsatisfactory scores. Students often experience difficulties in building the main ideas of writing and arranging words in writing persuasive texts. The application of the Student Team Achievement Division Cooperative model is expected to help students overcome difficulties in determining words, main ideas, and students' ways of thinking during the learning process. Prior to the use of the learning model, the results of writing persuasive text students obtained scores below the minimum completeness criteria (KKM) but after the application of the STAD type cooperative model student scores increased. Subsequent research uses a qualitative descriptive method, namely collecting data in written form according to facts and objects that are appropriate from the results of the approach taken. This study took a sample of 20 class VIII A students of SMPN 3 Ngamprah. From the results of students' ability to write persuasive texts in this study, an overall score of 1663 was obtained with an average score of 83. 17 students received a score of "Very Good" and 3 students received a score of "Good". The lowest score on student ability results is 77, while the average score is 85, and the highest score is 91. So learning persuasive text material using the Cooperative model type Student Team Achievement Division can be said to be successful.